PERCEPTIONS OF UNDERGRADUATE STUDENTS TOWARDS VIDEO CONFERENCE-BASED ENGLISH COURSES - Rahmawati, Indah; Kurniawan, Eri (TELL - US JOURNAL, 2023)
This study aimed to investigate the perception of undergraduate students enrolled in a private university in Bandung, regarding video conference-based English courses. The study utilized a quantitative approach by employing a questionnaire to collect data from a group of 116 undergraduate students in their seventh semester. The questionnaire was designed to identify students' perspectives on video conference-based English courses, focusing on aspects such as course benefits and identified drawbacks. The study found that the participants positively perceived video conference-based English courses. The participants agreed that the courses offered several benefits, including increased flexibility, reduced cost and reduced commuting time. However, participants also highlighted drawbacks related to technical challenges and reduced opportunities for face-to-face interaction. These results underline the adaptability of higher education in response to the video conference-based courses serving as a viable alternative to traditional in-person instruction. This study has implications for both educational policymakers and teachers. By recognizing the perceived benefits and drawbacks, Policymakers may consider the possibilities of developing regulations that encourage the integration of technology and remote learning into the broader curriculum. Furthermore, educators can refine their instructional strategies to align more closely with students' preferences and needs, ultimately enhancing the quality of remote education.